Progress in the Relationship between Vitamin D Deficiency and the Incidence of Type 1 Diabetes Mellitus in Children - Lian-Ping He; Yu-Xin Song; Ting Zhu; Wei Gu; Chang-Wei Liu (Journal of Diabetes Research)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease, due to a large number of islet β cells damaged, resulting in an absolute lack of insulin, ultimately relying on insulin therapy. Vitamin D is a fat-soluble sterol derivative that not only participates in calcium and phosphorus metabolism but also acts as an immunomodulatory role by binding to nuclear vitamin D receptors to regulate the expression of transcription factors. Increasing evidence has shown that vitamin D has immunoregulation and anti-inflammatory effects, and it may play a role in T cell regulatory responses due to downregulation in the expression of cathepsin G and inhibition of CD4+ T cell activation and protection of β cells from immune attack and is beneficial in decreasing oxidative stress in T1DM patients. Epidemiologic evidence demonstrates involvement of vitamin D deficiency in T1DM pathogenesis, with the immune system improperly targeting and destroying its own islet β cells. In addition, polymorphisms in genes critical for vitamin D metabolism may increase the risk of islet autoimmunity and T1DM. In this paper, the relationship between vitamin D deficiency and the molecular mechanism of T1DM was discussed.